2016
DOI: 10.1017/s2045796016000202
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and predictors of health service use among people with mental disorders in São Paulo metropolitan area, Brazil

Abstract: The great majority of individuals with an active mental disorder in São Paulo were either untreated or insufficiently treated. Awareness and training programmes to GM professionals are advocated to improve recognition, care take and referral to specialty care when needed. Proper integration among HC sectors is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 59 publications
(60 reference statements)
0
22
2
2
Order By: Relevance
“…From the segment seen in the professional health sector, 70% attended specialized services and 40% generalist services (treatment at both services was possible). Those proportions were similar among each diagnosis within the anxiety and mood disorders group, but not for substance use, which showed an ever higher proportion of specialized service usage (90% vs. 15% of general health services) [ 47 ]. Another study from the same research [ 39 ] identified that around 40% of cases of MH issues treated in general health services received only medication, while a minority (9%) received a combination of medication and psychotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…From the segment seen in the professional health sector, 70% attended specialized services and 40% generalist services (treatment at both services was possible). Those proportions were similar among each diagnosis within the anxiety and mood disorders group, but not for substance use, which showed an ever higher proportion of specialized service usage (90% vs. 15% of general health services) [ 47 ]. Another study from the same research [ 39 ] identified that around 40% of cases of MH issues treated in general health services received only medication, while a minority (9%) received a combination of medication and psychotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Even after overcoming these initial barriers, subjects face additional obstacles on the healthcare system. Access to treatment is unequal, resources in the public health system are insufficient and misallocated, general practitioners are not adequately trained in mental health, the provision of specialized care is limited and services are not adequately integrated [ 65 – 67 ]. Stigma against personality disorders is also a common phenomenon among health care providers.…”
Section: Discussionmentioning
confidence: 99%
“…O Estudo São Paulo Megacity estimou que somente 23% dos indivíduos diagnosticados com algum tipo de transtornos de ansiedade obtiveram acesso a algum tipo de serviços 17 . Entre os indivíduos que buscaram por serviços em São Paulo, apenas uma reduzida parcela obteve cuidados em serviços especializados (médicos psiquiatras, psicólogos ou enfermeiras especialistas em saúde mental).…”
Section: Uso De Serviços De Saúdeunclassified
“…Além disso, a proporção de pacientes que utilizaram formas de terapia complementar ou alternativa (grupos de autoajuda, conselheiros religiosos e outros tipos de curandeiros) também foi limitada. Ainda que dados comparativos inexistem, esta taxa de uso de serviços deve ser considerada superior a outras regiões brasileiras 17 .…”
Section: Uso De Serviços De Saúdeunclassified